The Immediacy Act in Learning at Elementary School - Ahsan R Junaidi (Jurnal Pendidikan Humaniora, 2014)
Tindak Immediacy Guru dalam Pembelajaran di Sekolah DasarAbstract: The focus of this research is; (1) how the manifestation of acts of immediacy in the elementary school teachers in the context of improving the emotional involvement of students in various learning situations; (2) how the motif acts teacher immediacy in learning in elementary school. This study used a qualitative approach to the study follows the tradition of phenomenology. The collection of data through observation and in-depth interviews. Sources of research data are five teachers and twelve students. Qualitative data analysis refers to the four stages of data analysis in interpretative phenomenological analysis. This study found that teacher immediacy in the elementary acts manifested in five acts, namely (1) to give the award, (2) a touch, (3) help students, (4) friendly posture and (5) physical proximity. Making of teachers to follow immediacy motives goal is to create a positive emotional climate in learning. Positive emotional climate is characterized by the understanding between teachers and students, the feeling of comfortable to the students and the emotional ties between students and teachers. Teacher beliefs about the profession and the professional experience of teachers is a cause that encourages teachers motive to commit immediacy. Key Words: teacher immediacy, learning, elementary school Abstrak: Fokus penelitian ini adalah: (1) bagaimana manifestasi tindak immediacy guru di sekolah dasar dalam konteks meningkatkan keterlibatan emosional siswa dalam berbagai situasi pembelajaran; (2) bagaimana motif tindak immediacy guru dalam pembelajaran di sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan mengikuti tradisi penelitian phenomenology. Pengumpulan data melalui observasi dan wawancara mendalam. Sumber data penelitian adalah lima orang guru dan dua belas siswa. Analisis data kualitatif merujuk pada empat tahap analisis data pada interpretative phenomenological analysis. Penelitian ini menemukan bahwa tindak immediacy guru di SD dimanifes-tasikan dalam lima tindakan, yaitu (1) memberi penghargaan, (2) memberi sentuhan, (3) membantu siswa, (4) sikap tubuh ramah dan (5) kedekatan fisik. Pemaknaan guru terhadap motif tujuan tindak immediacy adalah menciptakan iklim emosional positif dalam pembelajaran. Iklim emosional positif ditandai adanya kesepahaman antara guru dan siswa, adanya perasaan nyaman pada siswa dan adanya ikatan emosi antara siswa dan guru. Keyakinan guru tentang profesinya dan pengalaman profesio-nal guru merupakan motif penyebab yang mendorong guru melakukan tindak immediacy.Kata kunci: immediacy guru, pembelajaran, sekolah dasar